Approved Drilling And Production Practice In Oklahoma And Kansas - J. R. McWilliams (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1926)
THE task of recovering most of the contents of an oil and gas reservoir economically presents many and varied problems. In order to attempt intelligently a solution to these problems, an understanding of fundamental physical laws is essential. As the pertinent facts needed in applying these laws to recovery problems are not readily obtainable, observation must be made and the data tabulated. Here, good judgment must be exercised, for at best the information is meager. The engineer is well fitted to undertake the task of solving this problem. In my opinion, the decision on the part of some production executives to allow the engineer to cope with the oil recovery situation and other problems, is an outstanding example of improvement in production methods. The executive head must make this decision or the qualified engineer will be working under a severe handicap with the present system of supervising the production of oil and gas. A qualified engineer should have not only the required technical training but also enough field experience to enable him to understand the difficulties encountered in producing oil and gas. Such a man tactfully cooperating with the practical oil man can greatly improve present methods of oil recovery. The realization that nature's forces have not been efficiently controlled in past recovery of petroleum deposits has recently brought distinct improvement in production methods. Papers are to be presented at this meeting discussing in detail improved methods of conserving gas in both flowing and pumping wells, and also methods of lifting oil after Nature's supply of gas has proved inadequate. The application of back pressure to producing oil wells has not, to my knowledge, been extensively applied in Oklahoma or Kansas up to the present time. Most of the flowing wells are allowed to flow through the casing until the rock pressure has been dissipated. However, some flowing wells have been tubed before the well stopped flowing through the casing. Recording pressure-gages can be installed to study well performance.